2007
DOI: 10.1136/gut.2006.099226
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow alcoholic hepatitis score identifies patients who may benefit from corticosteroids

Abstract: Introduction: There is no consensus on the pharmacological treatment of alcoholic hepatitis. The Glasgow alcoholic hepatitis score (GAHS) has been shown to be more accurate than the modified Maddrey's discriminant function (mDF) in the prediction of outcome from alcoholic hepatitis. This study aimed to determine whether the GAHS was able to identify those patients who would benefit from corticosteroids. Methods: 225 patients with an mDF greater than or equal to 32 from five hospital centres in the United Kingd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 12 publications
0
57
0
6
Order By: Relevance
“…Routinely collected demographic and laboratory data were used to calculate prognostic scores viz: The Model for End-Stage Liver Disease (MELD), [37]; the Glasgow Alcoholic Hepatitis Score (GAHS), [38] and the Lille score [39]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Patients self-categorised their current drinking behaviour at day 90 as (i) abstinent; (ii) drinking at low levels: men 24g/day; women: 16 g/day; (iii) drinking at moderate levels: men >24 but 60g/day; women >16 but 40 g/day; (iv) drinking at high levels: men >60g/day; women >40g/day.…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%
“…Routinely collected demographic and laboratory data were used to calculate prognostic scores viz: The Model for End-Stage Liver Disease (MELD), [37]; the Glasgow Alcoholic Hepatitis Score (GAHS), [38] and the Lille score [39]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Patients self-categorised their current drinking behaviour at day 90 as (i) abstinent; (ii) drinking at low levels: men 24g/day; women: 16 g/day; (iii) drinking at moderate levels: men >24 but 60g/day; women >16 but 40 g/day; (iv) drinking at high levels: men >60g/day; women >40g/day.…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%
“…Our case scored a total of 63, 14 and 9, respectively, compared to reference values of 32, 21 and 9. A mDF ≥ 32 and a GAHS score ≥ 9 identify patients with a very poor prognosis who have been reported to have had a good clinical response to corticosteroids [23] . Based on an mDF of 63 and a GAHS of 9, a corticosteroid regimen was instituted and then slowly progressive tapered down, on the basis of progressive clinical, laboratory and radiological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The GAHS score uses age, white blood cell count, urea level, PT ratio or INR, and bilirubin level to calculate a score between 5 and 12, with scores above 9 associated with poor prognosis. 12 The initial study showed an accuracy of 81%, with values on day 1 in predicting day 28 mortality. In a follow-up study, patients with scores of 9 or greater had significant reduction of mortality if they received corticosteroids.…”
Section: Diagnosismentioning
confidence: 99%
“…In a follow-up study, patients with scores of 9 or greater had significant reduction of mortality if they received corticosteroids. 12 The Lille model is used to predict the mortality in patients with severe AH who have received glucocorticoids for treatment. This model includes six variables (age, renal insufficiency [INR >1.3 or creatinine clearance <40], albumin, PT, bilirubin level, and bilirubin level on day 7) that are used to determine mortality at 6 months.…”
Section: Diagnosismentioning
confidence: 99%